Digitization and future of jobs in Nigeria - Ojikeya, Chinerezi Sergiuspaulus; Neemene, Goodluck; Akujobi, Leonard Chibuzo; Iwueze, Ifeanyi Moses (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
In this age of digital revolution, every progressive nation is strategically diversifying its educational, economic, and non-formal sectors towards creating a more digitally compliant and information technology-driven society. This paper studied digitization and the future of jobs in Nigeria. Ten companies and industries were selected from each of the ten industrial cities in Nigeria (Lagos, Port Harcourt, Onitsha, Nnewi, Aba, Jos, Abeokuta, Warri, Kano and Kaduna). From the responses to the research questions, it was discovered that presently there is a serious digital skill gap that needs to be filled. As digitization tends to increase, the use of robots will proliferate. Results showed that 85% of the companies surveyed affirmed that they would employ robots in the coming years. This implies that about 62.7% of the jobs will be undertaken by robots. The authors proposed the implementation of a humanism model in our educational curriculum. The balance between digitization and humanism enhances a more robust, digital-driven, progressive, and economically viable society.